Effect of low Voltage Electrical Stimulation and Storage Conditions on the Funtional Characteristics of Beef Used in Emulsion Type Products - Márquez Salas, Enrique; West, Roger (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Ten standard grade steers were used to determine the effect of low voltage electrical\stimulation and storage treatments on water holding capacity (WHC), emulsifying capacity (EC) and emulsion stability (ES) of beef used for emulsion type products. Five animals were slaughtered and the carcasses immediately stimulated and five were not stimulated and served as control. Fresh (3 d. O°C) and frozen (60 d, -16°C) beef trimmings from stimulated and nonstimulated carcasses were used to determine WHC, EC and ES of the meat protein. Low voltage stimulation effectively lowered the pH values of the stimulated sides when compared to control sides, and a low pH (5.9) high temperature (35OC) conditions were created. However, the ultimate pH value was not affected. Emulsifying capacites water holding capacities and emulsion stability were not affected by stimulation treatments, but by storage condition. Fresh meat gave higher emulsion stability.